The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0034-75902001000100004
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos fiscais da inflação na análise de projetos

Abstract: RESUMOA análise de projetos industriais, cujo horizonte de planejamento usualmente varia de cinco a vinte anos, normalmente está sujeita a fortes condições de incerteza. Uma importante condição de incerteza é o fenômeno inflacionário, contornado pela Engenharia Econômica com o artifício de se trabalhar com fluxos de caixa em valores constantes e juros reais, desconsiderando os efeitos da inflação. Entretanto, nos casos das análises feitas depois do imposto de renda, os montantes reconhecidos como despesas de d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We have identified that this scenario has not changed, even after many years. The constant currency premise is a limitation in the research and a simplification of the model, which distorts long-term decision analyses (Álvares, 2001;Souza & Kliemann Neto, 2012), mainly because income tax considers not only the real interest rate but also monetary corrections for inflation when calculating taxable income. This study is relevant in this sense.…”
Section: Introductionmentioning
confidence: 99%
“…We have identified that this scenario has not changed, even after many years. The constant currency premise is a limitation in the research and a simplification of the model, which distorts long-term decision analyses (Álvares, 2001;Souza & Kliemann Neto, 2012), mainly because income tax considers not only the real interest rate but also monetary corrections for inflation when calculating taxable income. This study is relevant in this sense.…”
Section: Introductionmentioning
confidence: 99%